Hunter Beattie (1876–1951): A Conscientious Objector at the Margins. Issue 2 (October 2021) - Dickson, Neil
Abstract : Glasgow was the Scottish city in which the Open Brethren movement grew most profusely. During the First World War, significant sections of the leadership of their assemblies supported the British war effort. One individual who stood apart from this was the evangelist and homeopath, Hunter Beattie. He was the leading individual in an assembly in the east end who launched an occasional periodical in which he expounded his pacifist views. His publication was criticized in a Sunday newspaper, and his subsequent military hearing and criminal trial was covered by the newspaper. Other leading Glasgow Brethren publicly disassociated themselves from his position, which, in turn, led to criticism of them by some Brethren non-combatants. As well as giving an example of the treatment of conscientious objectors during the First World War, the paper examines the positions adopted towards war by both Beattie and his antagonists, illuminating aspects of the Brethren, their social class and relationships to society. It examines how some Brethren rejected a completely marginal status in church and society, but others saw the attraction of the margins.